Possible selves in adolescence: Gender differences - Molina, María Fernanda (2019)
Background: In adolescence, multiple differences have been found in the way boys and girls perceive themselves. This leads to wondering about the way in which adolescents perceive themselves in the future, that is, the possible selves (PSs) that they can generate. Objective: To investigate the differences according to sex in the PSs of adolescents of the Autonomous City of Buenos Aires (CABA). Method: The participants were adolescents (n = 392) of both sexes (women = 54.9%) who attended secondary schools in the CABA (M = 14.92, SD = 1.52). The adolescents completed an open-ended questionnaire in which they were asked to make a list of their PSs when they finish high school. A thematic content analysis of responses and a frequency count of categories were conducted. Chi-Square and Mann-Whitney U tests were used to study the differences in content, diversity and balance in the PSs according to sex. Results: The four categories of PSs most mentioned by boys and girls were study, work, profession, lifestyle, and family and loved ones. However, there were differences in the proportion in which males and females generated PSs in several domains. On the other hand, women had more diversity in the expected and desired PSs than men. No differences were found in the balance of the PSs. Conclusions: There is a coincidence in the domains of the PSs mentioned by boys and girls. However, women have a wider view of themselves in the future, and the domain of family and loved ones is still more prevalent for them.